First report of a short in‐frame biallelic deletion removing part of the EGF‐like domain calcium‐binding motif in LTBP4 and causing autosomal recessive cutis laxa type 1C. Issue 11 (16th August 2022) - Ravel, Jean‐Marie; Comel, Margot; Wandzel, Marion; Bronner, Myriam; Tatopoulos, Aurélie; Renaud, Mathilde; Lambert, Laëtitia; Bursztejn, Anne‐Claire; Bonnet, Céline
Abstract: Cutis laxa (CL) is a rare connective tissue disorder characterized by wrinkled, abundant and sagging skin, sometimes associated with systemic impairment. Biallelic alterations in latent transforming growth factor beta‐binding protein 4 gene ( LTBP4 ) cause autosomal recessive type 1C cutis laxa (ARCL1C, MIM #613177). The present report describes the case of a 17‐months‐old girl with cutis laxa together with a literature review of previous ARCL1C cases. Based on proband main clinical signs (cutis laxa and pulmonary emphysema), clinical exome sequencing (CES) was performed and showed a new nine base‐pairs homozygous in‐frame deletion in LTBP4 gene . RT‐PCR and cDNA Sanger sequencing were performed in order to clarify its impact on RNA. This report demonstrates that a genetic alteration in the EGF‐like 14 domain calcium‐binding motif of LTBP4 gene is likely responsible for cutis laxa in our patient.